Designing a Model to Explain the Role of Customer Knowledge Management Strategy in Achieving Competitive Advantage in Iraq's Electronic Banking Sector - Almhemis, Wisam Yaseen Mohsin; Safari, Mohammad (Business, Marketing, and Finance Open, 2026)
This study aims to design and validate a Customer Knowledge Management (CKM) strategy model to enhance competitive advantage in Iraq’s electronic banking sector. The sector is at a pivotal stage, experiencing rapid digital adoption while facing technological disparities, limited customer feedback mechanisms, and an inconsistent regulatory environment. Using a mixed-methods approach, the research collected data from 314 employees across six major Iraqi banks—Al-Rafidain, Al-Rasheed, Trade Bank of Iraq, Bank of Baghdad, Iraqi Islamic Bank, and Mansour Bank—and analyzed it using Structural Equation Modeling (SEM). The findings reveal that CKM, particularly through utilization of customer insights, is a significant driver of competitive advantage, enabling banks to achieve higher customer retention and innovation even under resource constraints. Private banks leveraging CKM demonstrated superior performance (78% retention) compared to state banks (62%), highlighting the strategic importance of acting on available customer knowledge. However, technological disparities, especially in rural branches where 40% lack reliable internet, limit CKM’s effectiveness, while regulatory gaps further exacerbate inequities between urban and rural banks. The study’s results contextualize CKM for Iraq, showing that utilization-centric strategies can compensate for feedback and data limitations, aligning with global research yet adapted to local constraints. The proposed model emphasizes the interplay between CKM utilization, technological infrastructure, and regulatory context, offering practical guidance for Iraqi banks to enhance competitiveness and digital transformation. In conclusion, CKM is a cornerstone for achieving sustainable competitive advantage in Iraq’s e-banking sector, provided infrastructural and regulatory barriers are addressed to unlock its full potential.